Neuronal migration and protein kinases - Ohshima, Toshio (Frontiers in Neuroscience, 2015)
The formation of the six-layered structure of the mammalian cortex via the inside-out pattern of neuronal migration is fundamental to neocortical functions. Extracellular cues such as Reelin induce intracellular signaling cascades through the protein phosphorylation. Migrating neurons also have intrinsic machineries to regulate cytoskeletal proteins and adhesion properties. Protein phosphorylation regulates these processes. Moreover, the balance between phosphorylation and dephosphorylation is modified by extracellular cues. Multipolar-bipolar transition, radial glia-guided locomotion and terminal translocation are critical steps of radial migration of cortical pyramidal neurons. Protein kinases such as Cyclin-dependent kinase 5 (Cdk5) and c-Jun N-terminal kinases (JNKs) involve these steps. In this review, I shall give an overview the roles of protein kinases in neuronal migration.